PERILAKU BERPINDAH KONSUMEN ROKOK DI JABODETABEK: ROKOK KONVENSIONAL KE ROKOK ELEKTRIK - Ronald Sukwadi; Priscilla Priscilla (Universitas Ahmad Dahlan Indonesia, 2020)
In 2023, the use of e-cigarettes is predicted to be higher and growing compared to conventional cigarettes. Based on the behavior of e-cigarette users, it is interesting to examine whether the customer satisfaction, price, product quality, and user experience related to their switching behavior. Interview, observation and questionnaire were applied to collect the data. Questionnaires were distributed to 200 e-cigarette users in Greater Jakarta. Structural equation model (SEM) with LISREL 8.70 software was used to analyze the data. The results showed that customer satisfaction and product quality have no significant influence to switching behavior, and price and user experience have significant influence to switching behavior.